Beneficial effect of body weight control on left ventricular diastolic function in the general population: an analysis of longitudinal data from a health check-up clinic. (11th December 2017) - Lee, Seitetz C; Daimon, Masao; Di Tullio, Marco R; Homma, Shunichi; Hasegawa, Takahiro; Chiou, Sy Han; Nakao, Tomoko; Hirokawa, Megumi; Mizuno, Yoshiko; Yatomi, Yutaka; Yamazaki, Tsutomu; Komuro, Issei
Abstract: Aims: Left ventricular (LV) diastolic dysfunction may lead to heart failure. A high body mass index (BMI) is associated with worse LV diastolic function. However, knowledge of the longitudinal relation between changes in BMI and LV diastolic function is limited. Methods and results: We retrospectively identified 165 asymptomatic individuals (aged 60 ± 10 years, 55% male) with preserved LV ejection fraction, who underwent repeated health check-ups (median interval: 365 days) at our hospital between 2009 and 2012. The longitudinal data were analysed using a linear mixed-effects model adjusted for important clinical variables at baseline to evaluate the associations between changes in BMI and LV diastolic function from one visit to the next. Baseline characteristics were BMI, 23 ± 3 kg/m 2 ; E / E ʹ ratio, 9 ± 2; E ʹ velocity, 8 ± 2 cm/s; and left atrial (LA) volume index, 26 ± 8 mL/m 2 . Eighty-two of our participants had baseline LV diastolic dysfunction. In multivariable analyses, a BMI change was associated with a change in LV diastolic function. A one-unit decrease in BMI between consecutive visits corresponded to an average decrease in LA volume index of 0.80 mL/m 2 (95% confidence interval: 0.38, 1.23; P < 0.001), a decrease in E / E ʹratio of 0.11 (−0.015, 0.23; P = 0.086), and an increase in E ʹ velocity of 0.11 cm/s (0.18, 0.031; P = 0.006). Conclusion: Our study showed that there was an association between changes in BMI and LV diastolic function. A decrease in BMI corresponded to a significant decrease in LA volume index and a significant increase in E ʹ velocity.